1975
DOI: 10.1111/j.1471-4159.1975.tb07628.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF METHIONINE AND METHIONINE SULPHOXIMINE ON RAT BRAIN S‐ADENOSYL METHIONINE LEVELS

Abstract: Abstract— Rat brain SAM levels were markedly increased after methionine administration, whereas the convulsant, L‐methionine‐dl‐sulphoximine (MSO), produced a 35 per cent decrease in whole brain content of S‐adenosyl‐L‐methionine (SAM). When methionine was given in combination with MSO, SAM levels were not decreased. Studies on the regional distribution of SAM revealed only a small variation between regions (from 24 nmol/g in midbrain to 49‐5 nmol/g in striatum). SAM levels were reduced by about 50 per cent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1976
1976
2005
2005

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…Seizures associated with MSO have been attributed to altered methylation because coadministration of L-methionine prevented the decrease in S-adenosylmethionine (26) and in the occurrence of seizures (10) without decreasing glutamine synthetase activity (27). In our experiments, L-methionine was coadministered with MSO to avoid the potential confounding influence of seizure activity.…”
Section: Discussionmentioning
confidence: 99%
“…Seizures associated with MSO have been attributed to altered methylation because coadministration of L-methionine prevented the decrease in S-adenosylmethionine (26) and in the occurrence of seizures (10) without decreasing glutamine synthetase activity (27). In our experiments, L-methionine was coadministered with MSO to avoid the potential confounding influence of seizure activity.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the potential confounding influence of seizures, we co-administered L-methionine with MSO in an 8:1 molar ratio. Work by Sellinger et al (1968;Schatz and Sellinger, 1975;Sellinger et al, 1984) demonstrated that methionine coadministration at this ratio prevented MSO-induced seizures and associated reductions in Sadenosyl methionine without reducing the potency of GS inhibition by MSO.…”
Section: Astrocyte Swellingmentioning
confidence: 99%
“…injection of either 0.83 mmol/kg of MSO (Sigma-Aldrich, St. Louis, MO, USA) or sterile saline vehicle (2.5 ml/kg). L-Methionine (6.7 mmol/kg) was co-injected with MSO at a molar ratio of 8:1 to prevent seizures associated with high doses of MSO (Sellinger et al, 1968(Sellinger et al, , 1984Schatz and Sellinger, 1975). L-Methionine was dissolved in 100 mmol/l NaOH and titrated to a pH of 7.6 with HCl.…”
Section: Experimental Procedures Experimental Protocolmentioning
confidence: 99%
“…These have included studies on the effect of MSO on the cerebral metabolism of amino acids and ammonia (1-8), brain amines (9, 10), glycogen ( cortical slices (19), rat brain S-adenosyl-L-methionine levels (20), mouse cerebellar ammonia (7), and rat brain glutamine synthetase (3). MSO and methionine have also been shown to be uptake antagonists (21,22).…”
Section: Introductionmentioning
confidence: 99%